The effects of chronic ritanserin treatment on sleep and the neuroendocrine response to L-tryptophan. - Idzikowski, C; Cowen, P; Nutt, D; Mills, F (1987)
A previous study has shown that acute administration of the 5-HT2 receptor antagonist ritanserin doubles Slow Wave Sleep (SWS) and increases the prolactin (PRL) response to L-tryptophan (LTP). The present study investigated the effect of repeated ritanserin treatment on sleep, neuroendocrine response to LTP and 5-HT2 platelet receptor binding. After 2 weeks, ritanserin administration SWS was persistently increased but the PRL response to LTP was unchanged. Platelet 5-HT receptor binding was undetectable at the end of ritanserin treatment but recovered 2 weeks after drug withdrawal. The results suggest that ritanserin causes a sustained effect on the 5-HT mechanisms mediating SWS and on platelet 5-HT2 receptors. However, adaptation occurs to its effect on 5-HT-mediated neuroendocrine responses.